Metallodrugs in the battle against non-small cell lung cancer: unlocking the potential for improved therapeutic outcomes - Xu, Xianzhi; Dai, Feng; Mao, Yiting; Zhang, Kai; Qin, Ying; Zheng, Jiwei (Frontiers in Pharmacology, 2023)
Non-small cell lung cancer (NSCLC) remains a leading cause of cancer mortality worldwide. Platinum-based chemotherapy is standard-of-care but has limitations including toxicity and resistance. Metal complexes of gold, ruthenium, and other metals have emerged as promising alternatives. This review provides a comprehensive analysis of metallodrugs for NSCLC. Bibliometric analysis reveals growing interest in elucidating mechanisms, developing targeted therapies, and synergistic combinations. Classification of metallodrugs highlights platinum, gold, and ruthenium compounds, as well as emerging metals. Diverse mechanisms include DNA damage, redox modulation, and immunomodulation. Preclinical studies demonstrate cytotoxicity and antitumor effects in vitro and in vivo, providing proof-of-concept. Clinical trials indicate platinums have utility but resistance remains problematic. Non-platinum metallodrugs exhibit favorable safety but modest single agent efficacy to date. Drug delivery approaches like nanoparticles show potential to enhance therapeutic index. Future directions include optimization of metal-based complexes, elucidation of resistance mechanisms, biomarker development, and combination therapies to fully realize the promise of metallodrugs for NSCLC.